Comparison of micro-radiofrequency therapy and tolterodine for the treatment of newly diagnosed overactive bladder: A retrospective cohort study - Tang, Min; Liu, Jin; Zhao, Chesong; Wang, Chengming; Zhang, Qian; Du, Mulong; Meng, Xiaoxin; Li, Pu (Frontiers in Neuroscience, 2023)
Purpose This study aimed to retrospectively compare the efficacy and safety of micro-radiofrequency (RF) therapy through the urethra vs. oral tolterodine tartrate in the treatment of newly diagnosed overactive bladder (OAB). Materials and methods In this study, 46 patients who were newly diagnosed with moderate-to-severe OAB were included; 23 of them underwent the micro-RF treatment procedure, and the other 23 patients took tolterodine. Bladder diaries were recorded 3 days before treatment and during the follow-up period on 1, 3, and 7 weeks after micro-RF therapy or oral tolterodine. Micturition parameters including daily voiding times, daily urge urinary incontinence (UI) episodes, daily urgency episodes, mean volume per micturition, post-void residual volume (PVR), maximum urine flow rate (Qmax), overactive bladder symptom score (OABSS), and quality of life (QoL) score were analyzed. Results All 46 patients underwent either micro-RF or oral tolterodine treatment, as well as a complete follow-up. The incidence of adverse events in the micro-RF group was 8.7% (2/23), and that in the tolterodine group was 43.5% (10/23). The following two adverse events happened in the micro-RF group: an injury to the urethra during catheterization in a man and a urinary tract infection in a woman, both of which were relieved or disappeared after day 3. The adverse effects in the tolterodine group were mainly dry mouth (4/23), dysuria (5/23), and constipation (8/23), but none of the patients withdrew from the drug therapy. Compared to pre-therapy, all parameters of both groups, including daily voiding times, daily urgency episodes, mean volume per micturition, OABSS, and QoL score, demonstrated significant improvements during follow-up in 7 weeks after therapy, except for daily UI episodes in the tolterodine group, while the above parameters showed bigger improvements in the micro-RF group than in the tolterodine group. Besides, the general treatment efficacy of micro-RF was 73.9% (17/23), which was significantly better than tolterodine (10/23, 43.5%), and the difference was 30.4% [95% CI: 3.4–57.5%, p = 0.036]. Conclusion In this retrospective study, we found that micro-RF therapy is safe and more effective than oral tolterodine for newly diagnosed moderate-to-severe OAB in a short-term follow-up. Stronger evidence would be provided through a well-designed, prospective, randomized controlled trial.